Evaluating the evidence on sitting, smoking, and health: Is sitting really the new smoking? - Vallance, J.; Gardiner, P.; Lynch, B.; D'Silva, A.; Boyle, Terry; Taylor, L.; Johnson, S.; Buman, M.; Owen, N. (American Public Health Association, 2018)
© 2018 American Public Health Association Inc. All rights reserved. Sitting has frequently been equated with smoking, with some sources even suggesting that smoking is safer than sitting. This commentary highlights how sitting and smoking are not comparable. The most recent meta-analysis of sedentary behavior and health outcomes reported a hazard ratio of 1.22 (95% confidence interval [CI] = 1.09, 1.41) for all-cause mortality. The relative risk (RR) of death from all causes among current smokers, compared with those who have never smoked, is 2.80 (95% CI = 2.72, 2.88) for men and 2.76 for women (95%CI = 2.69, 2.84). The risk is substantially higher for heavy smokers (< 40 cigarettes per day: RR= 4.08 [95% CI = 3.68, 4.52] for men, and 4.41 [95% CI = 3.70, 5.25] for women). These estimates correspond to absolute risk differences ofmore than 2000 excess deaths from any cause per 100 000 persons per year among the heaviest smokers compared with never smokers, versus 190 excess deaths per 100 000 persons per year when comparing people with the highest volume of sitting with the lowest. Conflicting or distorted information about health risks related to behavioral choices and environmental exposures can lead to confusion and public doubt with respect to health recommendations.